(untitled) (International Journal of Innovative Technologies in Economy, 2025)
Understanding Technology in the Context of National Development: Critical Reflections by Tiwari, Kostenko, and Yekhanurov (2025) has quickly gained academic and pedagogical significance. The work offers a comprehensive examination of how digital transformation and technological innovation intersect with national development strategies, governance models, and economic growth. It situates technology as both a driver of progress and a subject of critical reflection within development economics and ICT4D (Information and Communication Technologies for Development). Drawing on key policy frameworks including OECD’s digital transformation guidelines, United Nations (UN) development agendas, and the Network Readiness Index the authors analyze themes such as technological advancements, human capital, governance, and innovation ecosystems. The review finds that the book makes a valuable contribution to debates on digital transformation and development by identifying thematic pillars, capturing stakeholder insights, elaborating on twin foundations of tech enabled growth, and proposing concrete solutions to governance and inclusion challenges. This is shown by its adoption as post graduate course material for Industrial & Organizational programs at Universiti Malaysia Sabah (UMS), Malaysia and Esa Unggul University, Indonesia, where the author is associated with and currently using the book for post graduate studies courses listed in the curriculum. The curricular integration underscores the book’s broader pedagogical relevance in Southeast Asia. In doing so, it bridges theoretical discourse with practical policy considerations, providing scholars, policymakers, and practitioners a timely resource aligned with global development frameworks.